2018
DOI: 10.3390/app8071174
|View full text |Cite
|
Sign up to set email alerts
|

Low-Velocity Impacts on a Polymeric Foam for the Passive Safety Improvement of Sports Fields: Meshless Approach and Experimental Validation

Abstract: Over the past few years, foam materials have been increasingly used in the passive safety of sport fields, to mitigate the risk of crash injury. Currently, the passive safety certification process of these materials represents an expensive and time-consuming task, since a considerable number of impact tests on material samples have to be carried out by an ad hoc testing apparatus. To overcome this difficulty and speed up the design process of new protective devices, a virtual model for the low-velocity impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Increased attention on the negative effects of sports concussions and recent advances in technology have resulted in a number of innovative theoretical approaches being developed in order to analyse impacts in a sports context [22,23]. Approaches have to include laboratory simulations, human tests, and tests with animals [22][23][24][25]. Whyte et al (2019) provided a comprehensive review of impact testing for sports headgear and highlighted the need for experimental validation in all theoretical approaches [23].…”
Section: Introductionmentioning
confidence: 99%
“…Increased attention on the negative effects of sports concussions and recent advances in technology have resulted in a number of innovative theoretical approaches being developed in order to analyse impacts in a sports context [22,23]. Approaches have to include laboratory simulations, human tests, and tests with animals [22][23][24][25]. Whyte et al (2019) provided a comprehensive review of impact testing for sports headgear and highlighted the need for experimental validation in all theoretical approaches [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, EVA has a relatively low cost when evaluated for a similar polymer group such as thermoplastic polyurethane [27]. Foams made from EVA exhibit high impact resistance, vibration absorption capacity, and great recoverability characteristics after compression due to their viscoelastic nature [28][29][30]. Chang et al [31] demonstrated that the impact absorption is better by EVA foam when compared with the same density EPP foam when used as cushioning materials for bulletproof plates.…”
Section: Introductionmentioning
confidence: 99%
“…Three articles in the issue cover materials for safety devices. The first of these articles was authored by Penta and coworkers [12], and showcases a meshless approach for modelling the impact response of polymeric foam crash mats, with implications for the design of foam protective devices. The meshless approach allowed the crash mat model to function under high strain deformation, where elements within a mesh are prone to distortion.…”
mentioning
confidence: 99%